2021
DOI: 10.3389/fmicb.2021.633276
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Culture Improves Egg Quality and Reproductive Performance of Aged Breeder Layers by Regulating Gut Microbes

Abstract: This study aimed to investigate the effects of dietary yeast culture (YC) supplementation on egg production, egg quality, reproductive performance, immune functions, antioxidant capacity, and intestinal microbial structure of aged hens. A total of 224 Hy-Line Brown layers (54 weeks old) were randomly assigned to two dietary treatments. The control group was fed a basal diet and the YC group was supplemented with YC at 2.0 g/kg of their diet. Each group had seven replicates with 16 hens each. The study was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 75 publications
6
20
0
Order By: Relevance
“…Meanwhile, the PCoA showed a clear separation between the CE and DC groups, which indicated that multiple enzymes could dramatically alter the gut microbiota with increasing microbial evenness without decreasing microbial richness ( Zhang et al, 2017 ). Consistent with the results of previous studies, Firmicutes, Proteobacteria, and Bacteroidetes were the dominant phyla in the ileum of hens, accounting for more than 98% of the total bacteria ( Pan and Yu, 2014 ; Liu et al, 2021 ). The genera Lactobacillus , Enterococcus , Streptococcus , and Faecalicoccus were the signature taxa of the CE group determined using LEfSe (LDA > 4, p < 0.05).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, the PCoA showed a clear separation between the CE and DC groups, which indicated that multiple enzymes could dramatically alter the gut microbiota with increasing microbial evenness without decreasing microbial richness ( Zhang et al, 2017 ). Consistent with the results of previous studies, Firmicutes, Proteobacteria, and Bacteroidetes were the dominant phyla in the ileum of hens, accounting for more than 98% of the total bacteria ( Pan and Yu, 2014 ; Liu et al, 2021 ). The genera Lactobacillus , Enterococcus , Streptococcus , and Faecalicoccus were the signature taxa of the CE group determined using LEfSe (LDA > 4, p < 0.05).…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, CE administration significantly increased the serum HDL-C and T-AOC content and decreased the AST content. The T-AOC reflects the cumulative effect of all antioxidants in the blood and body fluids ( Suresh et al, 2009 ; Liu et al, 2021 ). Breeding hens frequently face oxidative stress and ovarian aging problems in the later laying stage, which considerably affect their performance and physiology ( Liu et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism promotes chicken performance ( Shang et al, 2013 ). These findings are consistent with those reported by Liu et al (2021) , who stated that dietary yeast culture supplementation, improves the biosynthesis of glutathione metabolism, lipopolysaccharide proteins, and ubiquinone and other terpenoid–quinone metabolic pathways which are prominent pathways associated with immune function, egg production, and reproductive efficiency in aged breeder hens ( Liu et al, 2021 ). Therefore, delta- and gamma-tocopherol, Phylloquinone, Acetylcholine, 3-Succinoylpyridine, and 1-Naphthol were validated and targeted for biosynthetic metabolic pathway engineering to improve the performance, gut health, and egg quality of aged breeder chickens.…”
Section: Discussionsupporting
confidence: 92%
“…Numerous studies showed that yeast can improve the richness and evenness of intestinal microbiota and promote production performance and gut health [ 27 , 28 ]. Several previous studies demonstrated that yeast can improve the abundance of Lactobacillus in the gut, which can improve the level of intestinal mucosal immunity and reduce intestinal inflammatory response by regulating the intestinal flora, thereby alleviating DM symptoms [ 29 , 30 , 31 ]. As reported previously, anisodamine has been widely used to relieve intestinal, microvascular, and airway smooth muscle spasms and effectively inhibit smooth muscle contractility, GI and sweat secretion [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, compared with the other groups, the probiotics group showed decreased eggshell strength ( p < 0.05). In previous studies, yeast was usually added to the feed, which the chickens consumed and digested slowly [ 11 , 29 ]. However, in this study, yeast was dissolved in water and administered by gavage at two fixed times on each day.…”
Section: Resultsmentioning
confidence: 99%